Evolution: ctenophore genomes and the origin of neurons - Marlow, Heather; Arendt, Detlev (Current biology, 2014)
Summary Recent sequencing of ctenophore genomes opens a new era in the study of this unique and phylogenetically distant group. The presence of neurodevelopmental genes, pre- and postsynaptic modules, and transmitter molecules is consistent with a single origin of neurons.